2015
DOI: 10.1136/gutjnl-2014-308932
|View full text |Cite
|
Sign up to set email alerts
|

POU2F2-oriented network promotes human gastric cancer metastasis

Abstract: Background and aimsAberrant upregulation of POU2F2 expression has been discovered in metastatic gastric cancer (GC). However, the mechanisms underlying the aberrant upregulation and the potential functions of POU2F2 remain uncertain.DesignThe role and mechanism of POU2F2 in GC metastasis were investigated in gastric epithelial cells, GC cell lines and an experimental metastasis animal model by gain of function and loss of function. Upstream and downstream targets of POU2F2 were selected by bioinformatics and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 42 publications
4
47
0
Order By: Relevance
“…Especially, specific promoters in LM2‐4175 were significantly enriched in as many as 19 factors, such as TFAP2C, POU2F2 and LMO4, and most of these factors were up‐regulated in LM2‐4175. Both POU2F2 and TFAP2C are proved critical regulators of tumorigenicity, EMT and metastasis, suggesting the reliability of our epigenetic analysis for identifying master regulators. However, the function of LMO4 in lung metastasis was rarely reported, and still needed further evaluation.…”
Section: Resultsmentioning
confidence: 90%
“…Especially, specific promoters in LM2‐4175 were significantly enriched in as many as 19 factors, such as TFAP2C, POU2F2 and LMO4, and most of these factors were up‐regulated in LM2‐4175. Both POU2F2 and TFAP2C are proved critical regulators of tumorigenicity, EMT and metastasis, suggesting the reliability of our epigenetic analysis for identifying master regulators. However, the function of LMO4 in lung metastasis was rarely reported, and still needed further evaluation.…”
Section: Resultsmentioning
confidence: 90%
“…[6][7][8][9][10] Recent studies indicate that the inactivation of this pathway is associated with the progression of several cancer types, [11][12][13] including pancreatic cancer, 14 breast cancer, 15 as well as lung tumours. 19,20 Ubiquitin-specific protease 33 (USP33), a member of ubiquitinspecific protease family, was initially identified as a substrate molecule which binds to VHL E3 ligase. A number of studies supported the notion that Slit-Robo signalling plays an important role in anti-tumour processes.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis identified that percentage of apoptotic cells in the OE group was significantly increased compared with the Upregulation of ZBTB7A suppresses cell migration. The migratory and invasive ability is another key characteristic of GC cells, which facilitates metastasis to other organs and results in a poor prognosis in patients (29,30). In the present study, the migration assay test was used to investigate the potential impact of upregulation of ZBTB7A on GC cell migration (Fig.…”
Section: Gain-of-function Of Zbtb7a In Sgc-7901 Cell Line Induces Apomentioning
confidence: 99%